2014
DOI: 10.1016/j.jviromet.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phi29-based whole genome amplification and whole transcriptome amplification in dengue virus

Abstract: Dengue virus is responsible for 50-100 million new infections annually worldwide. The virus uses error-prone RNA polymerase during genome replication in a host, resulting in the formation of closely related viruses known as quasispecies. The availability of next-generation sequencing technology provides opportunities to analyze viral quasispecies. Before analysis, it is crucial to increase the amount of DNA because of the limited amounts of viral genomic material that can be isolated from a patient. However, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The National Human Genome Research Institute project to identify functional elements in the human genome (Encyclopedia of DNA Elements, or ENCODE) identified functionality in much of the human genome previously without known utility (Consortium et al, 2007 ; Qu and Fang, 2013 ; Kellis et al, 2014 ) The double-stranded DNA genomes of HAdV also contain regions with no known function. Transcriptional profiling of host gene expression has been studied after HAdV infection (Dorer et al, 2011 ) However, although viral transcriptomes have been reported for several viruses, most notably dengue, varicella zoster, and Epstein-Barr viruses (Ortmann et al, 2008 ; Ertl et al, 2011 ; Nagel et al, 2011 , 2013 ; Arvey et al, 2013 ; Sujayanont et al, 2014 ), a de novo HAdV transcriptome has not been reported. Wu and coworkers used deep RNA sequencing to confirm known bat AdV transcripts (Wu et al, 2013 ), but did not investigate “noncoding” regions.…”
Section: Transcriptomementioning
confidence: 99%
“…The National Human Genome Research Institute project to identify functional elements in the human genome (Encyclopedia of DNA Elements, or ENCODE) identified functionality in much of the human genome previously without known utility (Consortium et al, 2007 ; Qu and Fang, 2013 ; Kellis et al, 2014 ) The double-stranded DNA genomes of HAdV also contain regions with no known function. Transcriptional profiling of host gene expression has been studied after HAdV infection (Dorer et al, 2011 ) However, although viral transcriptomes have been reported for several viruses, most notably dengue, varicella zoster, and Epstein-Barr viruses (Ortmann et al, 2008 ; Ertl et al, 2011 ; Nagel et al, 2011 , 2013 ; Arvey et al, 2013 ; Sujayanont et al, 2014 ), a de novo HAdV transcriptome has not been reported. Wu and coworkers used deep RNA sequencing to confirm known bat AdV transcripts (Wu et al, 2013 ), but did not investigate “noncoding” regions.…”
Section: Transcriptomementioning
confidence: 99%
“…Towards the limit of detection, it was more difficult to distinguish the signal from background for RCA when compared to TN-RCA (Figure S11A,B). This can be explained by incorporation of labelled dNTPs into accessible 3′-ends generated by the normal padlock and start primer and present in denatured HeLa genomic DNA (what is the basis of the whole genome amplification method [54]) and subsequent detection as background.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was shown that whole-transcriptome amplification techniques, which are based on multiple-displacement amplification, can be successfully used for amplification of RNA virus genomes ( 4 ). Because of the limited amount of viral genomic material available, a similar approach was employed here using the Quantitect whole-transcriptome kit (Qiagen) to increase the amount of cDNA necessary for sequencing the complete genome.…”
Section: Genome Announcementmentioning
confidence: 99%